SAT0004 EVALUATION OF AUTOPHAGY IN INFILTRATING AND CIRCULATING LYMPHOCYTES FROM PATIENTS WITH SJOGREN'S SYNDROME. (June 2019) - Colafrancesco, Serena; Minniti, Antonina; Priori, Roberta; Vomero, Marta; Barbati, Cristiana; Arienzo, Francesca; Iannizzotto, Valentina; Pipi, Elena; Campos, Joana; Nayar, Saba; Ciccia, Francesco; Barone, Francesca; et al.
Abstract : Background: Autophagy is a lysosome mediated catabolic process that promotes cell survival during stress conditions. Aberrant regulation of autophagy is involved in the pathogenesis of a widening spectrum of autoimmune disorders: in particular, activation of autophagy pathway is implicated in aberrant survival of activated T cells. We recently demonstrated that autophagy is up-regulated in CD4+ T lymphocytes from patients with Sjogren's Syndrome (SS) both in peripheral blood and tissue. Moreover, aberrant autophagy correlates with systemic disease activity. Little is known on the role of autophagy in B cells homeostasis in SS. Objectives: To investigate the activation of the autophagy pathway in lymphocytes infiltrating salivary gland in SS and peripheral blood from patients with SS. Methods: Frozen SS minor salivary glands (MSG) from 20 patients were sectioned and evaluated with immunohistochemistry (IHC) by staining for CD3+, CD20+, and CD21+. MSG sections, sequential to IHC, were stained by Cresyl Violet and microdissected (Laser Capture Microdissection) in order to isolate and collect small infiltrates, large CD21- infiltrates, and large CD21+ infiltrates (GC-like structures). Microdissected GC from frozen human tonsils were used as control. The expression of autophagy genes Atg5 and MAP1LC3II (expressed as 2^deltaCT normalized to GADPH) was determined by qPCR on microdissected tissue. For studies on peripheral blood, 19 SS patients and 11 healthy controls were enrolled, and autophagy, expressed as the ratio between Mean Fluorescence Intensity and the isotopic control (rMFI), was evaluated by Cyto-ID® Autophagy detection kit in T lymphocytes (CD4+ and CD8+) and B lymphocytes (CD19+) using a FACSCalibur cytometer. Results: Expression of the autophagy genes Atg5 and MAP1LC3 was significantly higher in the GCs from SS salivary glands compared to control tonsils (p<0.0001 and p=0.0013, respectively). In the salivary glands of SS patients, progressively higher expression levels of both Atg5 and MAP1LC3 mirrored the organization and severity of the inflammatory infiltrates (small vs. large CD21+ infiltrates p=0.0005 and p<0.0001 respectively). Immunophenotyping studies revealed activation of the autophagy pathway in both circulating CD19+ and CD4+ lymphocytes from SS (p=0.04 and p=0.03 compared to HC); conversely, no pathway activation was detected in CD8+ cells. Of note, in patients with SS activation of autophagy was most marked in circulating CD19+ B cells compared the other subsets [(CD19+ vs CD4+ (p<0.0001); CD19+ vs CD8+ (p= 0.001)]. Conclusion: Our findings revealed that the autophagy pathway is aberrantly activated in lymphocytes infiltrating salivary glands of SS patients. Of note, progressively higher expression levels of autophagy genes mirrored the severity and extension of inflammatory infiltrates. Immunophenotyping studies revealed that activation of autophagy is preeminent in B cells. Thus, activation of autophagy emerges as a feature of both infiltrating and circulating SS lymphocytes, and as mechanism possibly implicated in the activation and survival o?f autoreactive cells. Disclosure of Interests: Serena Colafrancesco: None declared, Antonina Minniti: None declared, Roberta Priori: None declared, Marta Vomero: None declared, cristiana barbati: None declared, Francesca Arienzo: None declared, Valentina Iannizzotto: None declared, Elena Pipi: None declared, Joana Campos: None declared, Saba Nayar: None declared, Francesco Ciccia Grant/research support from: CELGENE, PFIZER, Consultant for: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, Paid instructor for: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, JANSSEN, Speakers bureau: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, JANSSEN, MSD, ROCHE, AMGEN, Francesca Barone Grant/research support from: GlaxoSmithKline, Roche, UCB Pharma, Actelion, ONO Pharmaceutical, Consultant for: GlaxoSmithKline, Roche, Actelion, ONO Pharmaceutical, Guido Valesini: None declared, cristiano alessandri: None declared